Pengaruh Media Sosial Terhadap Budaya Toleransi dan Perdamaian di Kalangan Gen-Z - Husna Aulia Almadani; Mutiara Islami; Aan Andresari; Dadan Mardani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The rapid development of social media has influenced patterns of interaction, information dissemination, and the formation of public opinion, including among Generation Z. As a generation that grew up in the digital era, Gen Z has broad access to various cultural and social perspectives, which has the potential to strengthen values of tolerance and peace. This study aims to analyze the influence of social media on the development of a culture of tolerance and peace among Gen Z. The research method used is qualitative with a field study approach, involving 10 informants selected purposively. Data were collected through in-depth interviews and observation, then analyzed qualitatively in a descriptive manner through data reduction, data presentation, and conclusion drawing. The results indicate that social media can serve as an effective medium for spreading values of tolerance and peace, but it also has negative potentials such as the spread of hate speech and radicalization. In conclusion, the influence of social media largely depends on how it is used; wise utilization can strengthen a culture of tolerance and maintain social harmony in society.